Case-Based Learning in Forensic Accounting Education - Saputra, Komang Adi Kurniawan (Universitas Malikussaleh, 2019)
This study aims to examine the influence of the case based learning method application and motivation toward understanding of forensic accounting with emotional intelligence as moderator. The population of this research is the undergraduate students of accounting department who have taken forensic accounting course at Warmadewa University. Sampling technique in this research is purposive sampling with certain criteria such the student who have taken forensic accounting course. The research design is survey research design by distributing questionnaires to respondents. Data analysis uses a moderated regression analysis (MRA). The results of this research shows that the application of case-based learning method and motivation have a significant positive effect on forensic accounting comprehension, and it is proved that emotional intelligence is able to moderate the influence of application of case based learning method and motivation toward the understanding of forensic accounting